The Adjectival and Verbal Forces at Play in Present and Past Participles: A Cross-Linguistic Approach - Cantorna, Rocío (Bridging Cultures, 2022)
This paper explores the split nature of participles, which may show verbal or adjectival forces depending on the particular context in which they appear. It briefly refers to some problems of categorization affecting participles and points out certain ways in which participles with full adjectival force can be distinguished from those with verbal force as well as some of the limitations to the proposed tests. Moreover, it uses a cross-linguistic approach, resorting to translation into Spanish as a tool for the identification of participles with full adjectival force.